2020
DOI: 10.1111/nph.16882
|View full text |Cite
|
Sign up to set email alerts
|

Pollen analysis using multispectral imaging flow cytometry and deep learning

Abstract: Pollen identification and quantification are crucial but challenging tasks in addressing a variety of evolutionary and ecological questions (pollination, paleobotany), but also for other fields of research (e.g. allergology, honey analysis or forensics). Researchers are exploring alternative methods to automate these tasks but, for several reasons, manual microscopy is still the gold standard. In this study, we present a new method for pollen analysis using multispectral imaging flow cytometry in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 84 publications
3
66
0
Order By: Relevance
“…Recent studies have shown accuracies close to 100% (Bourel et al., 2020; Daood et al., 2016; Dunker et al., 2020; Sevillano & Aznarte, 2018), and even for a severe problem with 46 pollen types, Sevillano et al. (2020) arrived at a correct classification rate of nearly 98%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown accuracies close to 100% (Bourel et al., 2020; Daood et al., 2016; Dunker et al., 2020; Sevillano & Aznarte, 2018), and even for a severe problem with 46 pollen types, Sevillano et al. (2020) arrived at a correct classification rate of nearly 98%.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant progress has been made towards automated pollen analysis during recent years (e.g. Bourel et al., 2020; Dunker et al., 2020; Holt & Bennett, 2014; Sevillano et al., 2020), many field studies are still constrained by laborious and costly pollen identification and quantification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, several studies using machinelearning algorithms have been conducted to monitoring of the airborne pollen or to develop automatic classification system of pollen grains [19], [20], [21]. There are also many studies that have utilized CNN models to classify various pollen species [22], [23], [24], [25], [26], [27]. However, our research is focused on establishing a reliable method for assessing pollen viability using germination images rather than identifying the pollen species covered in the palynology fields.…”
Section: Introductionmentioning
confidence: 99%
“…This hierarchical interpretation of visual cues is also not unlike the way a traditional taxonomist might work to classify an organism, and deep learning is now being applied widely for automated species detection and ecosystem monitoring (reviewed in ref. 14 ) and was recently developed in a study of extant pollen ( 15 ). Romero et al ( 9 ) show how CNNs trained to identify modern taxa can be paired with imaging techniques to classify organisms deep in the fossil record.…”
mentioning
confidence: 99%